Targeting Ferroptosis Pathway to Combat Therapy Resistance and Metastasis of Cancer - Liu, Xuan; Zhang, Yiqian; Wu, Xuyi; Xu, Fuyan; Ma, Hongbo; Wu, Mengling; Xia, Yong (Frontiers in Pharmacology, 2022)
Ferroptosis is an iron-dependent regulated form of cell death caused by excessive lipid peroxidation. This form of cell death differed from known forms of cell death in morphological and biochemical features such as apoptosis, necrosis, and autophagy. Cancer cells require higher levels of iron to survive, which makes them highly susceptible to ferroptosis. Therefore, it was found to be closely related to the progression, treatment response, and metastasis of various cancer types. Numerous studies have found that the ferroptosis pathway is closely related to drug resistance and metastasis of cancer. Some cancer cells reduce their susceptibility to ferroptosis by downregulating the ferroptosis pathway, resulting in resistance to anticancer therapy. Induction of ferroptosis restores the sensitivity of drug-resistant cancer cells to standard treatments. Cancer cells that are resistant to conventional therapies or have a high propensity to metastasize might be particularly susceptible to ferroptosis. Some biological processes and cellular components, such as epithelial–mesenchymal transition (EMT) and noncoding RNAs, can influence cancer metastasis by regulating ferroptosis. Therefore, targeting ferroptosis may help suppress cancer metastasis. Those progresses revealed the importance of ferroptosis in cancer, In order to provide the detailed molecular mechanisms of ferroptosis in regulating therapy resistance and metastasis and strategies to overcome these barriers are not fully understood, we described the key molecular mechanisms of ferroptosis and its interaction with signaling pathways related to therapy resistance and metastasis. Furthermore, we summarized strategies for reversing resistance to targeted therapy, chemotherapy, radiotherapy, and immunotherapy and inhibiting cancer metastasis by modulating ferroptosis. Understanding the comprehensive regulatory mechanisms and signaling pathways of ferroptosis in cancer can provide new insights to enhance the efficacy of anticancer drugs, overcome drug resistance, and inhibit cancer metastasis.